Nujnost racionalizacije postopkov in dela v knjižnicah - Žaucer, Matjaž (Knjižnica, 2007)
The necessity of the rationalization of work and procedures in libraries due to the altered requirements and needs of users and due to the expected aggravated demands of the environment are displayed in the article. The causes for the changes in the librarianship and the causes for the changes in the environment are stated. The article analyzes the searching procedure in the Slovenian union bibliographic and catalogue database using the UDC. Upon a practical experiment it was established that the users can not make a successful use of the UDC because neither on the web nor in the database there are freely accessible UDC tables; there are also no exact usage instructions available. The outcomes of some tests in public and academic libraries reveal that the assistance of librarians with retrievals by the UDC is unpractical, timeconsuming and does not always lead to the correct result. Based on an international comparison of foreign academic libraries and one Slovenian library, the latter shows a substantial ineffectiveness in cataloging which leads to the assumption of the highdemanding or incomplete cataloguing rules. The case of the digital patent documents in one of the libraries reveals the incapability of processing of a large amount of documents according to the existing rules. The conclusion of the article is the appeal for more rational cataloging rules, for the accessibility of cataloging records directly via web search engines and for an optional indication of the UDC in the records. However, as the conditions in Slovenian libraries are not critical yet, the author has doubts about a quick response to those appeals.
Keywords: knjižnice; katalogizacija; klasifikacija; vsebinska obdelava; vsebinski katalogi; UDK; racionalizacija